Online Child Sexual Exploitation and Abuse (OCSEA) of Children and Adolescents: A Systematic Literature Review - Novianti, Novianti; Chusairi, Achmad (Universitas Islam Indonesia, 2024)
Internet can be dangerous since it has become a new medium for sexual crimes against children and adolescents. This study aimed to investigate online child sexual exploitation and abuse (OCSEA) of children and adolescents. It also identified the vulnerability factors contributing to OCSEA and explored the measures to prevent and address this challenge. In this study, a systematic literature review method was used, along with the formation of PICO, language terminology, inclusion and exclusion criteria, and data collection through PRISMA. The literature review showed that OCSEA vulnerability factors included young age, perception, communication, economy, accessibility, emotional stability, population, gender, parental supervision, and children’s internet knowledge. Even though there were relevant policies, the process of handling vulnerability was still at the stage of developing framework, necessitating new and comprehensive laws to address OCSEA more explicitly. Therefore, the limited prevalence data and evidence on OCSEA prompted this study to conduct a literature review to better understand the concept, development, and context.